PENGARUH PENDIDIKAN IBU DAN PENDAPATAN KELUARGA TERHADAP STATUS GIZI ANAK PRASEKOLAH DI TK DHARMA WANITA KERJO KIDUL, NGADIROJO, WONOGIRI - Indriastuti, Dwi; Handono, Nugroho Priyo (Akademi Keperawatan Giri Satria Husada Wonogiri, 2015)
Bagkraund : Pre educated childrent come on a group that denotesthe fast body growt, that is why it needs a high nutrition substances.Â Children of this age are usually sufferea from protein and calory malnutrition as know of PCM. The mother education and family income percapita are both so unseparatedly in the background.Target : To determine the effect of knowledge and toward the influence of the mother education and the family income percapita to the nutrition status of the pre educatet children at the dharma wanita mayor country ngadirojo, in the wonogiri regency either partially or simultaneously.Metodh : The study used cross ectional approach using analytic the research was conduted in studens of Dharma Wanita Kindergarten school cindegarten Kerjo Kidul, Distric Ngadirojo, in the Wonogiri Regency. Total population of 18. As well as total population. Teknik analisis of the data used to test linear regression analysis.Result : (1) There are positive and signivicant influences of the mother education to the nutritions status of the pre educated children, value of 0,000; (2) There are positif and signivicant family income percapitaÂ to the nutritions status of the pre educated children, value of 0,000; (3)There are positif and signivicant influence of the mother educationand the family income percapita to the nutrion status of the pre educated children. Conclusions : The effect of influence of the mother educationand the family income percapita to the nutrion status of the pre educated children either partiali or simultaneously. Â Key Words : mother education, family income percapita, children nutrition status